A stable solid-state lithium–oxygen battery enabled by heterogeneous silicon-based interface. (16th April 2023) - Yu, Zhiqian; Wang, Sheng; Zhu, Ting; Lin, Zijie; Li, Zhihuan; Zhang, Pei; Song, Hucheng; Li, Wei; Xu, Ling; Xu, Jun; Chen, Kunji
Abstract: Solid-state lithium-metal batteries using inorganic solid-state electrolyte (SSE) instead of liquid-electrolyte, especially lithium–oxygen (Li-O2 ) battery, have attracted much more attention due to their high-energy density and safety. However, the poor interface contact between electrodes and SSEs makes these batteries lose most of their capacity and power during cycling. Here we report that by coating a heterogeneous silicon carbide on lithium metal anode and Li1.5 Al0.5 Ge1.5 P3 O12 (LAGP)-SSE, a good interface contact is created between the electrode and electrolyte that can effectively reduce the interface impedance and improve the cycle performance of the assembled battery. As a result, the solid-sate Li-O2 battery demonstrates a cycle lifespan of ∼78 cycles being at least 3-times higher than the solid-state Li-O2 battery without silicon carbide with a capacity limitation of 1000 mAh g −1 at 250 mA g −1 . The characterization of discharge products indicates a typical two-electron convention of oxygen-to-lithium oxide for the solid-state Li-O2 battery system. This work paves a way for developing high-energy long-cycle solid-state lithium-metal battery. The work provides insights into the interface between the Li-metal and SSE to develop high-energy long-cycle all solid-state Li-metal batteries.